Seks dan Kuasa dalam Hukum Islam: Studi Fiqh Seksualitas - Millah, Ziinatul (De Jure: Jurnal Hukum dan Syari'ah, 2017)
This article aims to the discourse of sexuality and power in assessing the relationship between husband and wife sexuality that is often considered lame. The study of this article uses a type of socio-legal research by combining a conceptual approach in normative legal science and discourse analysis in the social-humanities sciences. In the perspective of the fiqh of sexuality, the coercion or sexual violence of the husband that befell his wife, limited as a sexual object, is actually an anti-monotheistic act. The relationship between husband and wife should be as a partner, as clothing (libas) which mutually bandage in channeling sexual desire, and give each other peace. There should be equality of husband and wife sexual relations based on willingness and agreement of both parties and affectionate with good treatment among others (mu'asyarah bi alma'ruf).Artikel ini mengkaji wacana seksualitas dan kuasa dalam menilai relasi seksualitas suami-istri yang sering kali dianggap timpang. Kajian artikel ini menggunakan jenis penelitian sosio-legal dengan memadukan pendekatan konseptual (conceptual approach) dalam ilmu hukum normatif dan analisis wacana (discourse analysis) dalam ilmu sosial-humaniora. Dalam perspektif fikih seksualitas, pemaksaan atau kekerasan seksual suami (marrital rape) yang menimpa istri, sebatas sebagai objek seksual, sejatinya merupakan tindakan antitauhid. Hubungan antara suami dengan istri seharusnya adalah sebagai partner, sebagai pakaian (libas) yang saling membalut dalam menyalurkan hasrat seksualnya, maupun saling memberi ketenangan. Harus ada kesetaraan relasi seksualitas suami-istri berdasarkan kerelaan dan kesepakatan kedua pihak dan penuh kasih sayang disertai perlakuan baik antar sesama (mu’asyarah bi alma’ruf).ne" This article aims to the discourse of sexuality and power in assessing the relationship between husband and wife sexuality that is often considered lame. The study of this article uses a type of socio-legal research by combining a conceptual approach in normative legal science and discourse analysis in the social-humanities sciences. In the perspective of the fiqh of sexuality, the coercion or sexual violence of the husband that befell his wife, limited as a sexual object, is actually an anti-monotheistic act. The relationship between husband and wife should be as a partner, as clothing (libas) which mutually bandage in channeling sexual desire, and give each other peace. There should be equality of husband and wife sexual relations based on willingness and agreement of both parties and affectionate with good treatment among others (mu'asyarah bi alma'ruf). Artikel ini mengkaji wacana seksualitas dan kuasa dalam menilai relasi seksualitas suami-istri yang sering kali dianggap timpang. Kajian artikel ini menggunakan jenis penelitian sosio-legal dengan memadukan pendekatan konseptual (conceptual approach) dalam ilmu hukum normatif dan analisis wacana (discourse analysis) dalam ilmu sosial-humaniora. Dalam perspektif fikih seksualitas, pemaksaan atau kekerasan seksual suami (marrital rape) yang menimpa istri, sebatas sebagai objek seksual, sejatinya merupakan tindakan antitauhid. Hubungan antara suami dengan istri seharusnya adalah sebagai partner, sebagai pakaian (libas) yang saling membalut dalam menyalurkan hasrat seksualnya, maupun saling memberi ketenangan. Harus ada kesetaraan relasi seksualitas suami-istri berdasarkan kerelaan dan kesepakatan kedua pihak dan penuh kasih sayang disertai perlakuan baik antar sesama (mu’asyarah bi alma’ruf).